Tc-99m-MDP- and F-18-FDG-Avid Metastatic Liver Lesion The Similarities and Differences Between 2 Modalities - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2012)
Although Tc-99m-MDP uptake in the extraskeletal tissues was presented before in the literature, FDG PET/CT and conventional bone scan findings have not been discussed together yet. Herein, we presented Tc-99m-MDP- and F-18-FDG-avid metastatic liver lesion in a breast cancer patient and compared 2 modalities in terms of tracer uptake.
Keywords: Tc-99m MDP bone scan; F-18-FDG PET/CT; breast cancer; liver metastasis; MDP UPTAKE; TECHNETIUM-99M-MDP